Two-dimensional β-cobalt hydroxide phase transition exfoliated to atom layers as efficient catalyst for lithium-oxygen batteries. (10th August 2018) - Sun, Zemin; Lin, Liu; Yuan, Mengwei; Li, Huifeng; Sun, Genban; Nan, Caiyun; Ma, Shulan; Yang, Xiaojing
Abstract: Metal-oxygen batteries, especially Li-oxygen batteries (LOBs), have attracted tremendous research attentions in the past decades. It is necessary to design novel cost-effective catalysts in the development of high performance rechargeable LOBs. Herein, we prepare the atom-layered two-dimensional (2D) β -Co(OH)2 nanosheets (AL- β -Co(OH)2 ) via phase transition of layered α- Co(OH)2 nanosheets ( α- Co(OH)2 ) in a mild wet chemical process. The thickness of AL- β- Co(OH)2 is less than 1.5 nm. It is the first time of using atom-layered β -Co(OH)2 in the system of LOBs and this material shows outstanding catalytic performance. The AL- β -Co(OH)2 nanosheets as electrocatalysts in LOBs can better reduce the over-potential, enhance the specific capacity and improve cycling capability. It demonstrates a high initial capacity 11841 mAh g −1 at a current density of 100 mA g −1 . It displays long cycle stability more than 70 cycles with a capacity restriction of 1000 mAh g −1 . These results suggest that this strategy for designing oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) catalysts via exfoliation of materials to atom-layered level could be a promising way to improve the performance of LOBs. Graphical abstract: Through phase transition exfoliation of layered α -Co(OH)2 nanosheets to obtain atom-layered two-dimensional β -Co(OH)2 nanosheets showing outstanding electrocatalytic properties in Li-O2 battery which gives a new way to improve ability for LOBs by exfoliation of 2D materials. Image 1 Highlights: Atom-layered β -Co(OH)2 nanosheets are prepared via phase transition exfoliation of α -Co(OH)2 . The overpotential is decreased through the exfoliation. The atom-layered β -Co(OH)2 nanosheets show significant improvement in the cyclic stability and specific capacity. It gives a new way to improve ability for LOBs by exfoliation of 2D materials.